Implementasi Good Governance dalam Pengelolaan Anggaran Pendapatan dan Belanja Desa (Studi Kasus: Desa Bantan Sari dan Desa Deluk Kabupaten Bengkalis) - Novira Sartika; M. Lazuardi (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
The purpose of this study was to determine the implementation of good governance, especially the principles of transparency, accountability and participation in the management of the Village Budget (APB Desa) for the 2019 fiscal year in Bantan Sari and Deluk based on Bengkalis Regent Regulation Number 53 of 2018 and its obstacles. The data used are primary data and secondary data. The research method used is descriptive qualitative analysis. This type of research is qualitative research. The results of this study indicate that Bantan Sari Government in managing APB Desa has not fully implemented good governance, especially the principle of transparency at the planning step and the reporting and accountability step. This is evidenced in both steps of the absence of information regarding APB Desa and reports on the implementation of APB Desa to the community through information media such as banners, announcement boards, billboards, official websites and so on. Meanwhile, the Deluk Government in managing the Village APB has not fully implemented good governance, especially the participatory principle, in which the community's ability to be involved in the decision-making process in the management of APB Desa is only 40%. The obstacles faced by the Bantan Sari Government in managing APB Desa was the slow process of disbursing APB Desa, inconsistent regulations and a lack of coordination between the BPD and the Government. While the obstacles faced by the Deluk Government in managing APB Desa was the changes in the price of goods every time they carry out an activity program, changes in weather, limitations in the budget and the delay in ratifying the budget ceiling.Â Keywords: Good Governance, Transparency, Accountability, Participation, APB Desa.